Advancing integrative "one-health" approaches to global health through multidisciplinary, faculty-led global health field courses. (March 2015) - Olsen, C; Conway, J; DiPrete-Brown, L; Hutchins, F; Poulsen, K; Solheim, K; Kraus, C; Gaus, D; Silawan, T
Abstract: Background: Since 2003, the University of Wisconsin-Madison Global Health Institute, together with collaborating campus and in-country partners, has offered immersive, multidisciplinary, faculty-led, global health field courses in Ecuador and Thailand. These courses aim to help students to develop a working understanding of integrative one-health approaches and acquire the skills to work effectively across disciplines. That is, we aim to foster an appreciation of the role of culture in perceptions of health, disease, and health care; the complex interactions of animal-human-ecosystem health and disease; and the value of integrating cross-disciplinary and cross-cultural perspectives and skills to solve complex public health problems. Methods: Students from various University of Wisconsin-Madison health faculties travelled, lived (accommodation included homestays in indigenous or rural communities), learnt, and engaged in community-health assessments or service-learning projects as a multidisciplinary team. We recruited students through annual presentations in each University of Wisconsin school or college and through recommendations from past participants. We recorded student reflections during the course, at course completion, and after graduation. Findings: Between 2003 and 2014: 215 students from the University of Wisconsin have taken part in the global health field courses. Students came from the fields of human medicine (53 [25%]), veterinary medicine (35 [16%]), nursing (40 [19%]), pharmacy (41 [19%]), and other degree programs (46 [21%]). Results of the in-course and post course assessments consistently show strong student satisfaction with many aspects of the programme, including safety, faculty mentorship, the value of the multidisciplinary approach, depth of learning, and programme cost. Former participants also report use of cross-cultural skills in their professional practice, work with populations from cultures other than their own, positive effects on their decisions for career activities, and the belief that immersive cross-cultural experiences should be a required part of professional training for all health professional students. Finally, the courses undergo independent programme evaluations (including in-country observation and interviews with participants and stakeholders) approximately every 5 years. Interpretation: Programme directors continue to seek improvements related to: sustainable faculty engagement from various disciplines; development of increasingly specific course group learning objectives, competencies, and assessment tools; sustainability of impacts on community-level health and wellbeing; continuity between University of Wisconsin-Madison and in-country university and community partners; and scholarship support and other approaches so that cost does not exclude interested students from participating. Funding: The GHI is supported through a combination of university, grants, and philanthropic funding; these field courses do not have specific, separate funding. Students self-fund participation in the courses.